2019
DOI: 10.3390/cancers11091308
|View full text |Cite
|
Sign up to set email alerts
|

GLUT1 and TUBB4 in Glioblastoma Could be Efficacious Targets

Abstract: Glioblastoma multiforme (GBM) is the most aggressive and deadly brain tumor, portending a median 13-month survival even following gross total resection with adjuvant chemotherapy and radiotherapy. This prognosis necessitates improved therapies for the disease. A target of interest for novel chemotherapies is the Warburg Effect, which describes the tumor’s shift away from oxidative phosphorylation towards glycolysis. Here, we elucidate GLUT1 (Glucose transporter 1) and one of its associated binding partners, TU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…This role becomes even more important when axons spike at higher frequencies. Interestingly, it has been reported that TUBB4A interacts with glucose transporter‐1 (Guda et al, 2019). It should still be proved whether the mutation in TUBB4A in patients with H‐ABC modifies this interaction and if metabolic changes could contribute to the physiopathology of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This role becomes even more important when axons spike at higher frequencies. Interestingly, it has been reported that TUBB4A interacts with glucose transporter‐1 (Guda et al, 2019). It should still be proved whether the mutation in TUBB4A in patients with H‐ABC modifies this interaction and if metabolic changes could contribute to the physiopathology of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several research groups have demonstrated that, in order to perform (i) harvesting of energy and replenishing the ‘nutrient (glucose) sink’ for a continuous, unchecked cellular proliferation; (ii) epithelial-to-mesenchymal transition (EMT); (iii) enhanced cell migration; and iv) increased angiogenesis, the cancer cells establish a preference for glycolytic metabolism—a so-called Warburg effect [ 13 , 14 , 15 ]. This metabolic reprogramming/shift from the oxidative phosphorylation to glycolytic pathway coupled with concomitant upregulated expression of the solute carrier 2 (SLC2) family of transporters (e.g., glucose transporter GLUT1, GLUT3, GLUT4) is the central hallmark of malignant gliomas [ 13 , 15 , 16 ]. While on one hand, it exerts a selective pressure for tumor survival in the tumor microenvironment, at the same time, it drastically perturbs the metabolic influx of glucose within the cell cytoplasm and in circulation (more importantly, blood plasma, which is supplying nutrients to the entire body).…”
Section: Introductionmentioning
confidence: 99%
“…Even when oxygen is abundant, and mitochondria are functioning, tumor cells obtain energy mainly through glycolysis, a process known as Warburg effect [1,2] . Glucose transporter (GLUT) is the main carrier mediating glucose uptake in cells, regulating glucose transmembrane transport [3] . Therefore, glucose uptake is an important rate‐limiting step in anaerobic fermentation of cancer cells.…”
Section: Introductionmentioning
confidence: 99%